2016
DOI: 10.1515/geo-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

Geohazards (floods and landslides) in the Ndop plain, Cameroon volcanic line

Abstract: Abstract:The Ndop Plain, located along the Cameroon Volcanic Line (CVL), is a volcano-tectonic plain, formed by a series of tectonic movements, volcanic eruptions and sedimentation phases. Floods (annually) and landslides (occasionally) occur with devastating environmental effects. However, this plain attracts a lot of inhabitants owing to its fertile alluvial soils. With demographic explosion in the plain, the inhabitants (143,000 people) tend to farm and inhabit new zones which are prone to these geohazards.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Previous scientific data by [22] has revealed that the causes of floods in the area include natural causes (siltation, Although 40% of the respondents agreed that the population is educated on soil and water conservation methods, 53.3% affirmed that farming was carried out along the flood prone areas. This is in line with Wotchoko et al [22] who reported that 20% of the Ndop Plain is plantation land and that more people tend to farm near the main rivers. Also, most of the population holds a FSLC and might not properly master modern techniques of soil and water management.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous scientific data by [22] has revealed that the causes of floods in the area include natural causes (siltation, Although 40% of the respondents agreed that the population is educated on soil and water conservation methods, 53.3% affirmed that farming was carried out along the flood prone areas. This is in line with Wotchoko et al [22] who reported that 20% of the Ndop Plain is plantation land and that more people tend to farm near the main rivers. Also, most of the population holds a FSLC and might not properly master modern techniques of soil and water management.…”
Section: Discussionmentioning
confidence: 97%
“…Floods are the major hazard in the Ndop Plain due to its flat and extensive topography that make the easy evacuation of water difficult problem of space. Flood hazard may affect about 25% of the Ndop Plain, along a north-south stripe [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study area encompasses about 20 villages with a population density of 162.3 inhabitants/km 2 , according to the 2005 national institute of statistics census. The Mount Oku area plays a significant role in the northwest region in terms of infrastructure, grazing, and agriculture—therefore, it is important to better constrain the conditions that could lead to landslide disasters in that area and to provide indications allowing to prevent them [ 10 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Landslide studies conducted in Cameroon can be classified into four approaches. In the first approach, the authors studied landslide-predisposing factors including morphological, geological, hydrological, and geographical properties [ 15 , 22 , 23 ]. In this approach, no geotechnical characteristics of soils were taken into account, and landslide-conditioning factors were simplified.…”
Section: Introductionmentioning
confidence: 99%